2017
DOI: 10.1002/ceat.201600508
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Study of Grinding Media Flow in a Ball Mill

Abstract: An experimental and numerical study on the grinding media dynamics inside a baffled ball mill under different solid‐flow regimes, namely, cascading, cataracting, and centrifuging, is described. The Eulerian approach was used for all simulations and the boundary condition at the drum wall was investigated by means of the specularity coefficient parameter. This effort is an important approach in representing the particle‐wall interaction in a ball mill. The restitution coefficient of the balls was experimentally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 31 publications
(39 reference statements)
0
4
0
1
Order By: Relevance
“…Dissipation is governed largely by the fluid forces described in the following, so damping in the contact force has negligible effect on the dynamics. We choose a restitution coefficient (𝐶𝑂𝑅) of 0.5 to be consistent with the literature [37]. Given the high bead loading, it is assumed, following insights from previous work [38], that the main contribution to the overall stresses is that arising from direct bead-bead contacts, as opposed to bead-fluid interactions.…”
Section: Discrete Element Methods (Dem) 31 Contact Model With Lubrica...mentioning
confidence: 99%
“…Dissipation is governed largely by the fluid forces described in the following, so damping in the contact force has negligible effect on the dynamics. We choose a restitution coefficient (𝐶𝑂𝑅) of 0.5 to be consistent with the literature [37]. Given the high bead loading, it is assumed, following insights from previous work [38], that the main contribution to the overall stresses is that arising from direct bead-bead contacts, as opposed to bead-fluid interactions.…”
Section: Discrete Element Methods (Dem) 31 Contact Model With Lubrica...mentioning
confidence: 99%
“…The degree of grinding in the drum can be improved by knowing the solid particles' pathlines in the drum or their collision with the wall. The performed CFD study with the adopted Eulerian approach mechanism showed that at a high rotational speed of the BDM, the impact of the specularity (specular reflection) and restriction coefficient are the most significant [7]. The results show that the specularity and restitution coefficient mostly affect the wall of the ball drum mill.…”
Section: Literature Review and Problem Statementmentioning
confidence: 98%
“…The results of determining a position of the free surface of flow patterns of mono-and two-dispersed granular fill in a slow-rotating chamber, which were obtained by using video recording and calculated by applying the DEM method, are given in [28]. In paper [29], authors compared results of research into flow patterns of the ball fill of a rotating chamber under cascade, cataract, and centrifuge modes, which were received by employing the method of computational fluid dynamics in the Euler's statement and visual analysis of video recording data. Similar methods of numerical and experimental studies were applied in [30].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%